MIGRATION FROM MONOLITHIC ARCHITECTURE TO MICROSERVICE ARCHTECTURE: a systematic review of literature - Gervino, Mariana Trevisoli (Revista Interface Tecnológica, 2020)
The constant increase of the need for scalability of softwares, multi territorial teams and agility in the development process to enable faster and high quality deliveries, there is a growing demand for the migration from monolithic architecture to microservice architectute. The migration process is difficult and risky due to monolithic softwares are tightly coupled. This systematic review synthesizes scientific works for a study and better understanding of this architecture migration. During the research phase, 16 papers were performed, 10 of which analyzed, thus, summarizing in this paper reasons which leads companies to migrate from monolithic architecture, tools and practices used during the migration process and challenges faced.